The Use of Marketing Communication Tools in Promoting and Communicating the Cultural Identity of Phetchaburi’s Traditional Desserts: From Past to Present - Bunleas, Pichapop; Srisai, Suttanipa (Rajapark Journal, 2024)
This study aims to examine the use of marketing communication tools in conveying the cultural identity of Phetchaburi’s traditional sweets from the past to the present. It employs qualitative research methods, including documentary research and oral history, with data gathered from 16 key informants selected through purposive sampling. The research instruments include data recording forms and interview guides, and the data were analyzed using content analysis techniques. The findings reveal that 22 types of marketing communication tools have been used over time to convey the cultural identity of Phetchaburi’s sweets. These tools can be categorized into two phases: (1) short-term promotional strategies, which include the use of sales personnel, mass media, sales promotions, competitions, advertising, social media influencers, company visit demonstrations, special events organized by government agencies, fusion food, and business partnerships; and (2) long-term promotional strategies, encompassing public relations, award-based marketing, third-party endorsements, word-of-mouth marketing, experiential marketing, product certification, content marketing, packaging innovation, personal branding, corporate social responsibility (CSR) activities, the recognition of renowned local confectioners, and international certifications.